Clinical drug‐drug interaction assessment of ivacaftor as a potential inhibitor of cytochrome P450 and P‐glycoprotein. (27th August 2014) - Robertson, Sarah M.; Luo, Xia; Dubey, Neeraj; Li, Chonghua; Chavan, Ajit B.; Gilmartin, Geoffrey S.; Higgins, Mark; Mahnke, Lisa
Abstract Ivacaftor is approved in the USA for the treatment of cystic fibrosis (CF) in patients with a G551D‐CFTR mutation or one of eight other CFTR mutations. A series of in vitro experiments conducted early in the development of ivacaftor indicated ivacaftor and metabolites may have the potential to inhibit cytochrome P450 (CYP) 2C8, CYP2C9, CYP3A, and CYP2D6, as well as P‐glycoprotein (P‐gp). Based on these results, a series of clinical drug‐drug interaction (DDI) studies were conducted to evaluate the effect of ivacaftor on sensitive substrates of CYP2C8 (rosiglitazone), CYP3A (midazolam), CYP2D6 (desipramine), and P‐gp (digoxin). In addition, a DDI study was conducted to evaluate the effect of ivacaftor on a combined oral contraceptive, as this is considered an important comedication in CF patients. The results indicate ivacaftor is a weak inhibitor of CYP3A and P‐gp, but has no effect on CYP2C8 or CYP2D6. Ivacaftor caused non‐clinically significant increases in ethinyl estradiol and norethisterone exposure. Based on these results, caution and appropriate monitoring are recommended when concomitant substrates of CYP2C9, CYP3A and/or P‐gp are used during treatment with ivacaftor, particularly drugs with a narrow therapeutic index, such as warfarin.